Jamur yang Terdapat pada Saus Tomat yang digunakan pada Makanan di Kawasan Lapangan Tugu Kopelma Darussalam - Zuraidah Zuraidah; Rizky Ahadi; Hendrix Indra Kusuma; Rizqina Al-Kautsyari (Universitas Syiah Kuala, 2024)
A recent investigation revealed that a considerable quantity of tomato sauce remains in circulation that is unhygienic and poses a significant health risk when consumed. It is therefore necessary to conduct this research in order to ascertain the characteristics of the fungi found in tomato sauce consumed by the public. This research was conducted in the Lapangan Tugu Kopelma Darussalam area of Banda Aceh with the objective of identifying and analysing the characteristics of the fungi found in tomato sauce used in food in the Lapangan Tugu Kopelma Darussalam area. Furthermore, the results of the feasibility test, which were generated as a consequence of this research, are to be reviewed as a reference for mycology courses. This research employs a quantitative descriptive methodology. The sample for this study was tomato sauce used in fried egg rolls, fried potatoes and batagor in the Lapangan Tugu Kopelma Darussalam area of Banda Aceh. A descriptive analysis of the data pertaining to the types and characteristics of fungi was conducted. The research yielded six fungal species found in tomato sauce used in food in the Lapangan Tugu Kopelma Darussalam area: Aspergillus fumigatus, Aspergillus niger, Penicilium sp., Geotrichum candidum, Aspergillus sp. and Curvularia sp. The fungal species were differentiated based on macroscopic characteristics, namely colony shape, colony colour and conidia. In contrast, the microscopic characteristics encompass the positioning of the conidia, the morphology of the conidia, the conidiophores and the fungal vesicles.